EMPOWERING STUDENT’S CRITICAL THINKING BY APPLYING PROJECT BASED LEARNING - Ance Jusmaya; Winda Efyanto (Fakultas Bahasa dan Seni UNP, 2018)
This research is focused on fostering students’ critical thinking through Project-Based Learning. It is based on the findings of the previous studies which show that University students in Batam mostly still have low quality of Critical Thinking. The design of the research was quasi-experimental research that want to find out the effect of Project Based Learning towards Criical Thinking of University students in Batam. To know students’Critical Thinking, this research uses Critical Thinking test. There are three pre tests and post tests. The pre-test were used to see students’ Critical Thinking before having treatment and posttest are used to see the differences on students critical thinking after giving treatments.The subjects were the students of English Department of Putera Batam University who took Speaking class. The data found that Project Based Learning has a significant effect on students' Critical Thinking skills. This conclusion can be seen based on the analysis that has been done where t observed > t table. t observed = 3,83 and t table 2.36 with standard significant 0,05.Thus, it can be concluded that Criticak thinking skills can be increased by using Project Based Learning method.Keyword: Empowering, Project Based Learning, Critical Thinking,University Students.MENINGKATKAN KEMAMPUAN CRITICAL THINKING MAHASISWA DENGAN MENERAPKAN PROJECT BASED LEARNINGAbstrakPenelitian ini difokuskan pada pengembangan Critical Thinking mahasiswa melalui metode Pembelajaran Project Based Learning. Hal ini didasarkan pada temuan penelitian sebelumnya yang menunjukkan bahwa mahasiswa Universitas di Batam sebagian besar masih memiliki Critical Thinking yang rendah. Desain penelitian ini adalah penelitian kuasi-eksperimental yang ingin mengetahui pegaruh pembelajaran Project Based Learning terhadap Criical Thinking mahasiswa di Batam. Untuk mengetahui kemampuan Critical Thinking mahasiswa, penelitian ini menggunakan tes Critical Thinking. Melalui tiga kali pre tes dan pos test. Pre-test digunakan untuk melihat kemampuan Critical Thinking sebelum menjalani perlakuan dan posttest digunakan untuk melihat perbedaan skor Critical Thinking pada mahasiswa setelah diberikan perlakuan. Subjek penelitian adalah mahasiswa dari Jurusan Sastra Inggris Universitas Putera Batam yang mengambil kelas Speaking. Data yang ditemukan menunjukan bahwa Project Based Learning memiliki pengaruh yang signifikan terhadap kemampuan Critical Thinking mahasiswa. Kesimpulan ini dapat dilihat berdasarkan analisis yang telah dilakukan dimana t tabel ˂ t yang observed. t observed = 3,83 dan t tabel 2,36 dengan standar signifikan 0,05. Jadi, dapat disimpulkan bahwa kemampuan Critical Thinking dapat ditingkatkan dengan menggunakan metode pembelajaran Project Based Learning.Kata Kunci: Meningkatkan,Project Based Learning,Critical Thinking,Mahasiswa